Suicide in Psychiatric Inpatients— A Case–Control Study - Deisenhammer, Eberhard A.; Behrndt-Bauer, Elisa-Marie; Kemmler, Georg; Haring, Christian; Miller, Carl (Frontiers in Psychiatry, 2020)
Objective: Psychiatric inpatients constitute a population at considerably increased risk for suicide. Identifying those at imminent risk is still a challenging task for hospital staff. This retrospective case–control study focused on clinical risk factors related to the course of the hospital stay. Method: Inpatient suicide cases were identified by linking the Tyrol Suicide Register with the registers of three psychiatric hospitals in the state. Control subjects were patients who had also been hospitalized in the respective psychiatric unit but had not died by suicide. Matching variables included sex, age, hospital, diagnosis, and admission date. The study period comprised 7 years. Data were analyzed by the appropriate two-sample tests and by logistic regression. Results: A total of 30 inpatient suicide cases and 54 control patients were included. A number of factors differentiated cases from controls; after correction for multiple testing, the following retained significance: history of aborted suicide, history of attempted suicide, history of any suicidal behavior/threats, suicidal ideation continuing during hospitalization, no development of prospective plans, no improvement of mood during the hospital stay, and leaving ward without giving notice. Logistic regression identified the latter three variables and history of attempted suicide as highly significant predictors of inpatient suicide. Conclusions: Preventive measures during hospitalization include thorough assessment of suicidal features, an emphasis on the development of future perspectives, and a review of hospital regulations for patients who want to leave the ward.